Computing and Network Sustainability Proceedings of IRSCNS 2018 - Peng, Sheng-Lung.; Dey, Nilanjan; Bundele, Mahesh; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book offers a compilation of technical papers presented at the International Research Symposium on Computing and Network Sustainability (IRSCNS 2018) held in Goa, India on 30-31st August 2018. It covers areas such as sustainable computing and security, sustainable systems and technologies, sustainable methodologies and applications, sustainable networks applications and solutions, user-centered services and systems and mobile data management. Presenting novel and recent technologies, it is a valuable resource for researchers and industry professionals alike.
Snaring Cyber Attacks on IoT Devices with Honeynet -- Image Enhancement Using Morphological Operations: A Case Study -- Evaluation of e-NAM Adoption: A Case of Jetalpur Mandi, Gujarat -- A New Technique For Extrinsic Text Summarization -- Dynamic provisioning of Cloud resource based on workload prediction -- Conceptual Machine Learning Framework for Initial Data Analysis -- The Role of Social Factors in Education: A case study in Social Network Perspective -- Investigating the Effect of Compression and Decompression in Video using Fractal Technique.
Keywords: Telecommunication; Computer networks .; Data protection; Communications Engineering, Networks; Computer Communication Networks; Data and Information Security